PENGELOLAAN KONFLIK, PENDEKATAN HUMANISME - M Sayuri Rustam (Journal Competency of Business, 2017)
Conflicts will always arise in every organization. This occurs because of the different perceptions of each member of the goals to be achieved by the organization, competition and jealousy. The difference in perceptions between these members will bridge the differences in the activity programs that will be carried out by the organization, which in turn will lead to conflicts in the final results achieved. If this happens, the organization will be ineffective. Competition between organizational members is also one of the causes of conflict. Competition carried out in a healthy, honest and kind manner will provide great benefits for the organization. However, in many cases the competition that occurs is actually carried out in a way that is dishonest, unhealthy and unkind, to pursue purely personal interests and ignore the interests of the organization as a whole. As a result, the organization is running lame, because one member actually tackles other members for the sake of their individual interests. Jealousy of the good fortune between members is also a trigger for conflict. This jealousy may very well be triggered by unfair treatment by the leadership of the organization. Therefore, the attitude and behavior of organizational leaders must reflect the principle of justice for all members of the organization and take policies that can provide satisfaction to all parties. The best solution to this conflict is a win-win solution. This means that the parties to the conflict must be given the best solution so that they do not feel worse than others. Thus, the conflict is not prolonged and can be resolved immediately with a final solution that benefits all parties